Experimental investigation of the abnormal rise of water-wings downstream of a step-type aerator. Issue 4 (17th March 2022) - Han, Hu; Guobing, Huang; Zhixin, Wang; Lu, Huang
Abstract: In the prototype observation of a huge water conservancy project, flood discharge in the deep outlets showed strong fluctuations in the downstream of step-type aerators. Intermittent eruption and rise of the water-wing was observed, and the water-wing occasionally impacted on the structures above the chute. In order to investigate the mechanism of water-wing rise, model tests of the deep outlet have been conducted. High-speed camera, pressure sensors, and hot-wire anemometer are adopted to obtain the characteristics of cavity and water-wing. Several key parameters are measured, including air pressure in the cavity and air entrainment volume. It is found that variations of net cavity length, filling water length, and the height of water-wing rise increase with the angle ratio R, and a substantial jump occurs for all related parameters when R approaches 1.4. The rate of water-wing rise W is less than 10% for R < 1.4, while it suddenly increases to over 25% for R > 1.4. Correlations among inflow condition, jet impact angle, cavity deformation, pressure fluctuation in the cavity, and the rise of water-wing are studied, thus the underlying mechanism of abnormal rise of water-wing is proposed. HIGHLIGHTS: Abnormal rise of water-wing downstream of a step-type aerator is studied by the model test. The correlation among incoming flow conditions, aeration cavity length, filling water length, air entrainment volume, and water-wing rising has been studied. The mechanism of abnormal rise of the water-wing is revealed. Graphical Abstract